2016
DOI: 10.2139/ssrn.2831450
|View full text |Cite
|
Sign up to set email alerts
|

Score-Driven Systemic Risk Signaling for European Sovereign Bond Yields and CDS Spreads

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…D'Agostino and Ehrmann ( 2014 ) pointed to an overreaction of the market given the change in fundamentals and thus to a structural change in longer-term risk perception. Gross and Kok ( 2013 ); Alter and Beyer ( 2014 ); Broner et al ( 2014 ); Glover and Richards-Shubik ( 2014 ); Shoesmith ( 2014 ); Erce ( 2015 ); Li and Waterworth ( 2016 ); Lange et al ( 2017 ) discussed the relationships between private and public sector bonds, between sovereign bonds and credit derivatives, and the transmission channels between bank risk and sovereign risk. Gerlach-Kristen ( 2015 ); Blasques et al ( 2016 ); Ehrmann and Fratzscher ( 2017 ); Moessner ( 2018 ); Arakelian et al ( 2019 ) confirmed the stabilizing impact of ECB measures on bond spreads after 2012.…”
Section: Introductionmentioning
confidence: 99%
“…D'Agostino and Ehrmann ( 2014 ) pointed to an overreaction of the market given the change in fundamentals and thus to a structural change in longer-term risk perception. Gross and Kok ( 2013 ); Alter and Beyer ( 2014 ); Broner et al ( 2014 ); Glover and Richards-Shubik ( 2014 ); Shoesmith ( 2014 ); Erce ( 2015 ); Li and Waterworth ( 2016 ); Lange et al ( 2017 ) discussed the relationships between private and public sector bonds, between sovereign bonds and credit derivatives, and the transmission channels between bank risk and sovereign risk. Gerlach-Kristen ( 2015 ); Blasques et al ( 2016 ); Ehrmann and Fratzscher ( 2017 ); Moessner ( 2018 ); Arakelian et al ( 2019 ) confirmed the stabilizing impact of ECB measures on bond spreads after 2012.…”
Section: Introductionmentioning
confidence: 99%